Charge transfer and catalytic properties of various PEDOTs as Pt-free counter electrodes for dye-sensitized solar cells - Kurokawa, Yuki; Kumar Vats, Ajendra; Kato, Takehito; Shafie, Suhaidi; Pandey, Shyam S. (IOP Science, 2022)
Despite the high electrocatalytic activity of Pt and the fact it is a champion catalyst for the counter electrode (CE) of state-of-art dye-sensitized solar cells (DSSCs), its high cost, rarity, and the concern about its possible deterioration by the iodine-based redox electrolyte, has compelled the search for suitable and low-cost catalysts for CEs. To circumvent this issue, efforts were directed to exploring the suitability of various types of poly(3,4-ethylenedioxythiophene)(PEDOT)-based conducting polymers as the most suitable electrocatalysts for low-cost CEs. Amongst various types of PEDOT explored as CEs, micelle directed electropolymerized PEDOT:SDS (:sodium dodecyl sulfate) exhibited not only excellent catalytic activity (>Pt), as confirmed by cyclic voltammetry and electrical impedance spectroscopy investigations, but also fairly good photovoltaic performance exhibiting photoconversion efficiency of 5.8%, which is only slightly lower than the performance shown by Pt-based CE for the DSSCs fabricated under similar experimental conditions. Further improvement for the PEDOT:SDS-based CE surpassing the Pt-based CE is envisioned by morphological control and making their suitable composites with carbon-based nanomaterials.